Marketing Library and Information Resources and Services Using Social Media Platforms: The Security Question - Kaku, David; Adadu, Mary (My University, 2023)
Several social media platforms have emerged and revolutionised how library resources and services are marketed today. So many libraries have adopted the use of many of these media platforms for their library organizations. In this study; Marketing library and information resources and services using social media platform: The security question; the authors x-rayed the spread and use of social media in libraries examining the concepts of marketing, information resources and services, social media platforms and security in the information eco system. The authors discovered that, the most common security issues library organizations faced are data leakage and non-disclosure violations, cybersquatting where strangers masquerade as your library, your CEO or simply ‘own’ your trademark space in social media platforms amongst others. The study suggested amongst others that to safeguard malware; training on prevention, identification, containment, and eradication of malware be given to employees and individuals during their studies. Library organizations should be deliberate about empowering their policies by putting an investment in upgrading security tools that are well suited for the social media environment.
Keywords: Marketing; social media; security and information